If -π < arg (z) < -π/2, then arg bar z - arg bar (-z) is equal to (1) π (2) -π (3) π/2 (4) -π/2

Solution: 

If arg (z) = -π+θ

Then arg \(\bar{z}\) = π-θ

So arg \(\bar{z}\) – arg \(-\bar{z}\) = π-θ+θ

= π

Hence option (1) is the answer.

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

Ask
Question